Chemical and nutritional study leaves radish, Raphanus sativus L., as food for human consumption - Huamán Malla, J. (2003)
The presente work has been carried out with the leaves of tha rabanito Rsphanus Sativus L. The presence of tannins ot the catechol and coumarín was determined by qualitative analysis. The quantitative analysis showed the presence of minerals macronutrients: calcium, phosphorus,potasium,sodium and magnesíum; micronutrientes: iron; and traces of copper, aluminum manganese, boron, barium,chromium and zinc. The analysís ot vitamins determined the content on fresh sample of vitaminan A, 81 and C.